Characterization and potential mechanisms of resistance of cucumber genotypes toBemisia tabaci(Hemiptera: Aleyrodidae) - Novaes, Natalia S.; Lourencao, Andre L.; Bentivenha, Jose P. F.; Baldin, Edson L. L. [UNESP]; Melo, Arlete M. T. (Springer, 2020)
Bemisia tabaci(Genn.) (Hemiptera: Aleyrodidae) is a major pest of several agricultural crops, being vector of an extreme number of viruses. The broad variety of host plants, high adaptability and evolution of resistance to insecticides evidence the difficult in the management ofB. tabaciin the agriculture system. Host plant resistance is a valuable and sustainable method of insect management. To date, few studies have characterized the resistance of cucumber (Cucumis sativusL.) genotypes toB. tabaci, although this plant is one of the most preferred host of this hemipteran. The objective of this study was to assess the resistance of 60 cucumber genotypes againstB. tabaciin greenhouse and laboratory conditions and to characterize the mechanisms of resistance involved based on morphological and physical plant parameters. Initially, 12 genotypes were selected in a screening bioassay. In general, 'IAC-1214' expressed high levels of antixenosis to the insect, causing low attractiveness to adults and non-preference for oviposition and colonization. 'Wellington' prolonged the development of the insect and provoked low levels of adult emergence, expressing levels of antibiosis. Antibiosis and/or antixenosis were detected in 'IAC-1201', 'Campeiro', 'Japones', and 'IAC-1311', while antixenosis was detected in 'Kyria' and 'IAC-1175'. The density of the trichomes and the color of the leaves are described and discussed here. The selected genotypes present potential application in integrated programs that focus on reducing populations ofB. tabaciin the agricultural system and in breeding programs aiming to explore resistant genotypes against the insect.
Keywords: Antibiosis; Antixenosis; Trichomes; Leaf color parameters; Sweet potato whitefly